Escaping the Curse of Oil? : The Case of Gabon - Soderling, Ludvig (IMF Working Papers; Working Paper ;, 2002)
This paper studies the prospects for sustainable growth and economic development in Gabon, in the face of a severe decline in its main source of income and growth, id est oil. A simple Computable General Equilibrium model is used to simulate the development of the non-oil economy under various assumptions. The results of the simulations underline Gabon's dependence on foreign financing-especially private-and its vulnerability to variations in oil prices. The potential role of an income stabilization fund is also discussed.